Small fry ebook A memoir. - Brennan-Jobs, Lisa (2023)
The New York Times –bestselling memoir by Steve Jobs' daughter: "This sincere and disquieting portrait reveals a complex father-daughter relationship." — Publishers Weekly , starred review Born on a farm and named in a field by her parents—artist Chrisann Brennan and Steve Jobs—Lisa Brennan-Jobs's childhood unfolded in a rapidly changing Silicon Valley. When she was young, Lisa's father was a mythical figure who was rarely present in her life. As she grew older, her father took an interest in her, ushering her into a new world of mansions, vacations, and private schools. Lisa found her father's attention thrilling, but he could also be cold, critical and unpredictable. When her relationship with her mother grew strained in high school, Lisa decided to move in with her father, hoping he'd become the parent she'd always wanted him to be. Small Fry is Lisa Brennan-Jobs's poignant story of childhood and growing up. Scrappy, wise, and funny, Lisa offers an intimate window into the peculiar world of this family, and the strange magic of Silicon Valley in the seventies and eighties.